Diagnostic testing and the challenges associated with vaccine development for porcine rotavirus - Crowley, Abigail (Kansas State University, 2020)
Rotavirus (RV) is one of the leading causes of acute gastroenteritis worldwide in children and young animals. In swine, this disease commonly infects neonatal and recently weaned piglets. A RV infection can be either asymptomatic or symptomatic depending on the RV strain, age of the pig, the immune status of the piglet, and environmental conditions. When symptoms are present, they include dehydration, loss of weight, mild to severe diarrhea, slowed growth, and possible death. Swine producers can face economic losses due to loss in production and the costs associated with treating the infection. This report discusses the ever evolving field of swine diagnostic testing, the complexity of RV infections within swine populations, the difficulties in developing a cross-protective vaccine for RV infections, and possible vaccine strategies used in other host species that can help further swine vaccine development.
Keywords: Rotavirus; Swine; Diagnostics; Vaccines; Human